2017
DOI: 10.1080/0144235x.2017.1351672
|View full text |Cite
|
Sign up to set email alerts
|

Density functional theory of doped superfluid liquid helium and nanodroplets

Abstract: During the last decade, density function theory (DFT) in its static and dynamic time dependent forms, has emerged as a powerful tool to describe the structure and dynamics of doped liquid helium and droplets. In this review, we summarize the activity carried out in this field within the DFT framework since the publication of the previous review article on this subject [M. Barranco et al.,

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
116
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(119 citation statements)
references
References 290 publications
(280 reference statements)
3
116
0
Order By: Relevance
“…[32]. energy delocalization of the He atoms [20,28,86,87]. The intensity distribution among the rotational-vibrational lines enables an accurate determination of the temperature in He droplets of 0.37 K [32][33][34].…”
Section: Single Molecules and Small Clustersmentioning
confidence: 99%
See 1 more Smart Citation
“…[32]. energy delocalization of the He atoms [20,28,86,87]. The intensity distribution among the rotational-vibrational lines enables an accurate determination of the temperature in He droplets of 0.37 K [32][33][34].…”
Section: Single Molecules and Small Clustersmentioning
confidence: 99%
“…Over the years, the helium droplet community has published several reviews on vibrational and electronic spectroscopy, photoionization, and ultrafast dynamics [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]. Earlier spectroscopic studies revealed that embedded molecules, such as SF 6 [32] and OCS [33,34] undergo free rotation inside the droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical studies of the systems listed above usually follow 'atomistic' approaches, such as path-integral [14][15][16] and diffusion [17][18][19] Monte Carlo, as well as density functional theory [20,21], where the many-body environment is modeled as a cluster of finite size in real space. These approaches make it challenging to reach the thermodynamic limit, are prone to systematic errors due to a discrete time step, while also providing only a limited insight into the angular momentum properties of the individual components of the many-particle system.…”
mentioning
confidence: 99%
“…For example, the Orsay-Trento (OT) DFT can reproduce both static and dynamic response of superfluid helium at 0 K and it has been successfully employed in many applications. 33,34 Recently, OT-DFT was also used to model soliton propagation in superfluid helium to support the experimental observations. 29 In this work, we report on the properties of shock waves and bright solitons in bulk superfluid 4 He.…”
Section: Introductionmentioning
confidence: 99%